Maximal Tizanidine withdrawal managed with dexmedetomidine: a vital intervention - Marah Omer (21633203) (2024)
Tizanidine withdrawal is a rare and complex phenomenon characterized by a surge in adrenergic activity upon abrupt discontinuation of the drug. We present a unique case of a 41-year-old male with multiple comorbidities who self-administered an exceptionally high daily dose of Tizanidine, leading to severe withdrawal symptoms. This case report highlights the challenges in managing such cases. The patient, with a history of myofascial pain syndrome, hypertension, anxiety, and depression, experienced distressing symptoms, including tachycardia, rebound hypertension, neuropsychiatric manifestations, and involuntary muscle movements. Unlike previous cases, our patient required the addition of dexmedetomidine in conjunction with benzodiazepines for symptom management. Reintroduction of Tizanidine, carefully controlled and tapered, led to stabilization of hemodynamics and cessation of involuntary movements. This case underscores the importance of individualized treatment and vigilant monitoring when dealing with Tizanidine withdrawal, particularly at elevated daily doses. Other Information Published in: Oxford Medical Case Reports License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1093/omcr/omae005